An experimental investigation on the thermophysical properties of 40% ethylene glycol based TiO2-Al2O3 hybrid nanofluids. (July 2020) - Urmi, WajihaTasnim; Rahman, M.M.; Hamzah, W.A.W.
Abstract: This paper presents an experimental study on the thermophysical properties of 40% ethylene glycol-based TiO2 -Al2 O3 hybrid nanofluids. The hybrid nanofluids were prepared for concentrations of 0.02 to 0.1% and temperature of 30 to 80 °C. Nanofluid stability is studied using visual observation, spectral UV–Vis, zeta potential, and results obtained excellent stability. The rheological test was conducted to determine the Newtonian behaviour. The viscosity and thermal conductivity were investigated. Viscosity and thermal conductivity of hybrid nanofluids boost as opposed to the base fluid. The thermal conductivity is improved by 40.86% at 0.1% volume concentration and 80 °C. The hybrid nanofluids have higher thermal conductivity than single TiO2 and Al2 O3 and better heat transfer efficiency with a concentration greater than 0.04%. The newly developed models of viscosity and thermal conductivity are defined with good accuracy from the experimental data. The performance enhancement ratio shows that hybrid nanofluids with a concentration greater than 0.04% are advantageous due to having better efficiency in heat transfer. The combined effects of TiO2 and Al2 O3 nanoparticles on thermal behaviour, compared to viscosity, are more significant. Therefore, the practical application of hybrid nanofluids in heat transfer systems could have a potential influence for its increased thermal conductivity and low viscosity. Highlights: Thermophysical properties of the TiO2 -Al2 O3 hybrid nanofluids improved with temperature and concentration. Newtonian behaviour of hybrid nanofluids was analyzed with temperatures and concentrations. Overall thermal conductivity increase of 40.86% with concentration of 0.1% at 80°C. Thermal conductivity of hybrid nanofluids are superior to single nanofluids. Hybrid nanofluids are beneficial due to their increased heat transfer performance at concentrations above 0.04%.